Differentiation-dependent chromosomal organization changes in normal myogenic cells are absent in rhabdomyosarcoma cells - Ibarra, Joe; Hershenhouse, Tyler; Almassalha, Luay; Walterhouse, David; Backman, Vadim; MacQuarrie, Kyle L. (Frontiers in Cell and Developmental Biology, 2023)
Myogenesis, the progression of proliferating skeletal myoblasts to terminally differentiated myotubes, regulates thousands of target genes. Uninterrupted linear arrays of such genes are differentially associated with specific chromosomes, suggesting chromosome specific regulatory roles in myogenesis. Rhabdomyosarcoma (RMS), a tumor of skeletal muscle, shares common features with normal muscle cells. We hypothesized that RMS and myogenic cells possess differences in chromosomal organization related to myogenic gene arrangement. We compared the organizational characteristics of chromosomes 2 and 18, chosen for their difference in myogenic gene arrangement, in cultured RMS cell lines and normal myoblasts and myotubes. We found chromosome-specific differences in organization during normal myogenesis, with increased area occupied and a shift in peripheral localization specifically for chromosome 2. Most strikingly, we found a differentiation-dependent difference in positioning of chromosome 2 relative to the nuclear axis, with preferential positioning along the major nuclear axis present only in myotubes. RMS cells demonstrated no preference for such axial positioning, but induced differentiation through transfection of the pro-myogenic miRNA miR-206 resulted in an increase of major axial positioning of chromosome 2. Our findings identify both a differentiationdependent, chromosome-specific change in organization in normal myogenesis, and highlight the role of chromosomal spatial organization in myogenic differentiation.